Ethics of Collaboration: Comments on the AUCCCD White Paper. Issue 1 (2nd January 2021) - Keyes, Lee; Polychronis, Paul D.; Wallace, David; Brunner, Jon
ABSTRACT: Recently, the Association of University and College Counseling Center Directors (AUCCCD) published a White Paper on a multidimensional understanding of organizational structures for counseling centers (Mitchell, Oakley & Dunkle 2019). This article provided a historical overview of such structures, argued that there is no one optimal structure for all campuses, provided recommendations for factors to consider in related decision-making, and advocated for collaboration regardless of structure. The authors of this article extend the conversation by elaborating on some of the ethical issues involved in collaboration, as the White Paper did not address the limits of acceptability in such processes. Given that the authors are psychologists, we will be focusing on the Ethical Principles for Psychologists and Code of Conduct (2017) of the American Psychological Association (APA). Similar language can be found in the ethical codes of other mental health professionals, and we note these sources as well.